Selective Screening for the Factor V Leiden Mutation: Is it Advisable prior to the Prescription of Oral Contraceptives? - Schambeck, Christian M; Schwender, Stefan; Haubitz, Imme; Geisen, Ulrich E; Grossmann, Ralf E; Keller, Franz (Thrombosis and Haemostasis, 1997)
The cumulative thrombotic risk of Factor V (FV) Leiden and oral contraceptives (OC) recommends screening for the mutation. Assuming that a family history of thrombosis increases the patient’s likelihood of bearing FV Leiden, a selective rather than universal screening would be performed. We studied the utility of a family history of thrombosis for screening of FV Leiden before prescription of OC and, furthermore, the utility of screening even if oral contraception is favoured. 101 patients who had their first and single thromboembolic event while using OC were interviewed. 609 women without any history of thromboembolism recruited by gynecologists completed a standard questionnaire. 101 of these women, age-matched and currently using OC, were selected for a case-control study. Regarding patients with previous thromboembolism, a family history in a first-degree relative had a positive predictive value (PPV) of only 14% for FV Leiden. A PPV of 12% was calculated by investigating the 609 thrombosis-free women. Inherited FV Leiden (odds ratio = 4.9) and acquired risk factors (odds ratio = 10.1) were both found to be the most prominent, but independent additional risks. Nevertheless, FV Leiden carriers, both heterozygotes and homozygotes, did not suffer earlier from thromboembolism than patients without the mutation. In conclusion, family history is an unreliable criterion to detect FV Leiden carriers. Screening for factor V Leiden can be worthwhile even if the advantages of oral contraception are higher assessed than the thrombotic risk. Affected women knowing about their additional risk could contribute to the prevention of thrombosis in risk situations.